High transparency iron doped indium oxide (In2—xFexO3, x = 0.0, 0.05,0.25, 0.35 and 0.45) films prepared by the sol-gel method - Ibrahim, N.B.; Baqiah, H.; Abdullah, M.H. (Universiti Kebangsaan Malaysia, 2013)
High quality indium oxide and iron doped indium oxide nanocrystalline films were prepared by the sol-gel method followed by a spin coating technique. The samples were characterized by an X-ray diffractometer, an atomic force microscopy and a UV-vis spectroscopy. All samples had good crystallinity with a preferred orientation in the (222) direction. The crystallite size increased from 12.1 nm for the pure sample to 16.1 nm for the sample with x=0.35 and then decreased to 12.1 nm for the sample with x=0.45. All samples contained nanometer grain sizes with a smooth surface. All films showed a high transmission of over 91% in the wavelength range of 200-800 nm.